Integrability of a Time Dependent Coupled Harmonic Oscillator in Higher Dimensions - Singh, Ram Mehar; Bhardwaj, S B; Sharma, Kushal; Rani, Richa; Chand, Fakir; Malik, Anand (Discontinuity, Nonlinearity, and Complexity, 2026)
Within the frame work of extended complex phase space characterized by x = x1 + ip4,y = x2 + ip5,z = x3 + ip6, px = p1 + ix4, py = p2 + ix5 and pz = p3 +ix6, we investigate the exact dynamical invariant for a coupled harmonic system in three dimensions. For this purpose Lie-algebraic method is employed and the invariant obtained in this work may play an important role in reducing the order of differential equations, solution of Cauchy system and to check the accuracy of a numerical simulation.